Human Dendritic Cells Synergistically Activated by FVIII Plus LPS Induce Activation of Autologous CD4+ T Cells - Miller, Lilija; Ringler, Eva; Kistner, Klaus Maximilian; Waibler, Zoe; on behalf of the ABIRISK Consortium (Thrombosis and Haemostasis, 2018)
The most severe side effect in haemophilia A (HA) treatment is the development of anti-factor VIII antibodies, also called inhibitors. Why inhibitors develop in a proportion of treated HA patients and how this can be prevented remains largely unanswered. Among numerous theories, the presence of immunological danger signals, associated with events such as surgery or infection, has been proposed to play a role. In this study, we demonstrate that human dendritic cells (DC) synergistically activated by a combination of factor VIII (FVIII) concentrate plus the bacterial danger signal lipopolysaccharide (LPS) induce a significantly stronger activation of autologous CD4+ T cells than DC pretreated with FVIII or LPS alone. The observed T cell activation is dependent on antigen processing, presentation on MHC class II molecules and costimulation via CD86. Of note, FVIII plus LPS pretreated DC predominantly induce the activation of memory T cells and a minor proportion of naive T cells. Collectively, our data support a model in which immunological danger signals plus FVIII concentrates synergistically increase human CD4+ T cell responses to FVIII protein.
Keywords: anti-FVIII immune response; lipopolysaccharide; T cells; danger signal; inhibitors